Multi-disciplinary diagnosis and management of verrucous venous malformation of the right knee: a case report - H, Varun; Madke, Bhushan; Sharma, Prerit; Singh, Adarshlata; Mittal, Anurag; Tiwari, Vedashree Vedprakash (Frontiers in Radiology, 2026)
Verrucous Venous Malformations (VVMs) are a rare subtype of Congenital Vascular Malformations (CVMs) characterised by a hyperkeratotic, verrucous surface. We present the case of a ten-year-old male with a VVM localised to the right knee, which presented as a gradually enlarging, asymptomatic lesion since birth. A comprehensive, multi-modality diagnostic workup was performed, including thorough clinical evaluation, dermoscopy, radiologic imaging (Plain radiograph, colour Doppler ultrasonography and magnetic resonance imaging) and histopathological analysis with hematoxylin and eosin staining, along with immunohistochemical staining for CD-34. The lesion exhibited characteristic features consistent with VVM. The patient was managed by percutaneous sclerotherapy to reduce lesion size. This case highlights the importance of a multidisciplinary strategy in the diagnosis and management of VVMs to improve clinical outcomes.